Formação de professores e o desafio da inclusão de alunos com deficiência: caminhos trilhados por professoras dos anos iniciais - Vargas, Gisele Marques (2013)
The inclusion of students with disabilities in the regular school is a right provided for in the Federal Constitution and led, in many cases, a reorganization of that institution. Because they are the teachers the main professionals working with these students, his training becomes part key to improving the quality of education, having as the principle that everyone can come to receive students with disabilities in their classrooms said regular. Based on the theoretical framework of Pletsch (2009), Carvalho (2009), Mantoan (2006), Machado (2009) and Mittler (2003), this dissertation seeks to identify as there is the formation of teachers who work with students included and the perception of these about inclusion. The methodological process was routed through open interviews with four (04) teachers from early years of a State School, located in Pelotas/RS. The results show that, in general, the teachers did not have No preparation for dealing with the inclusion during the initial training, and training was given, especially when they had contact with the classes with students included. The main alternative training were by means of Information Technologies, pedagogical meetings held in the school and the presence of a teacher specialist for existing support that allowed them to converse and remedy doubts. Another point highlighted was referring to what we call for continued training institutionalized and continued training non-institutionalized. The first character with more individual and informal and the second, more formalized by means of courses or specific programs. The teachers emphasized have been changes to deal with inclusion. Made reference to the humanization of them to seek to understand the needs and pace of each one of his students, for example. It was possible to conclude that the teachers they found viable alternatives for their formation and that these alternatives have helped to ensure that the work with the inclusion would be most qualified. However, although if they consider prepared to work with the inclusion, the interviewees emphasize that the training of teachers still requires improvement and greater attention of the public agencies of education.